Effect of External Factors of Technology Acceptance Model Toward Technology Acceptance of Online Travel Agent - Waluyani, Risma Candra; Subroto, Bambang; Purnomosidhi, Bambang (Jurnal Economia, 2018)
Abstract: Effect of External Factors of Technology Acceptance Model Toward Technology Acceptance of Online Travel Agent. This study aimed to identify and analyse internal factors and external factors which affect the intention of Universitas Brawijaya students to use online travel agent service. Samples were selected by using nonprobability sampling technique and convenience sampling method. The instrument of this study was online questionaires whose result were analyzed by SEM-PLS. This study found that personal innovativeness and self-efficacy affected how students perceive that online travel agent service is easy to use and it is useful for them. Student’s perception, trust in online travel agent service, and information obtained from others affected students’ attitude to use online travel agent service. Furthermore, students who feels that online travel agent technology is useful for them will have positive attitude on the existence of online travel agent service and they wil also have intention to use the online travel agent service. Keywords: Online travel agent, behavioral intention, internal factors, external factors.Abstrak: Pengaruh Faktor Eksternal Technology Acceptance Model Terhadap Penerimaan Teknologi Online Travel Agent. Tujuan penelitian ini adalah untuk menguji faktor internal dan faktor eksternal yang mempengaruhi minat mahasiswa Universitas Brawijaya untuk menggunakan agen perjalanan online. Sampel penelitian dipilih menggunakan teknik nonprobability sampling dengan metode convenience sampling. Instrumen penelitian ini adalah kuesioner yang dibuat secara online dengan bantuan google form dan dianalisis dengan SEM-PLS. Hasil penelitian ini menunjukkan bahwa inovasi pribadi dan keyakinan sendiri mepengaruhi persepsi mahasiswa bahwa teknologi agen perjalanan online mudah digunakan, yang selanjutnya membuat mereka berpendapat bahwa teknologi agen perjalanan online berguna bagi mahasiswa. Persepsi mahasiswa bahwa teknologi agen perjalanan online berguna bagi mereka, kepercayaan terhadap teknologi agen perjalanan online, dan informasi yang diperoleh dari orang lain melalui internet mempengaruhi sikap mahasiswa untuk menggunakan teknologi agen perjalanan online. Selanjutnya mahasiswa yang berpendapat bahwa teknologi agen perjalanan online berguna bagi mereka akan bersikap positif atas adanya teknologi agen perjalanan online dan berminat untuk menggunakan teknologi agen perjalanan online. Kata kunci: agen perjalanan online, minat perilaku, faktor internal, faktor eksternal.